Why drivers refuse to yield: power of neutralization over deterrence in Chinese urban cross-walks - Yin, Chen; Ding, Naikan; Zhang, Jinrui; Shao, Zufeng; Tang, Chenggang (Frontiers in Future Transportation, 2025)
Drivers’ yielding behavior toward pedestrians is a key determinant of urban road safety. Although deterrence-based interventions such as fines and penalties are widely employed, little is known about the psychological rationalizations drivers use to justify non-compliance. To address this gap, this study integrates neutralization theory and deterrence theory to examine the determinants of yielding intentions. A structural equation model (SEM) was constructed using survey data from 400 licensed drivers in Wuhan, China, to evaluate the dual effects of neutralization techniques and deterrence mechanisms. The results show that three neutralization strategies—denial of injury, denial of victim, and defense of necessity—significantly undermine yielding intentions, while deterrence mechanisms such as formal sanctions and shame exert positive but comparatively weaker influences. Among these factors, denial of victim emerges as the strongest deterrent to yielding, and license-related penalties are perceived as more severe than monetary fines. Overall, the findings demonstrate that the negative impact of neutralization substantially outweighs the positive effect of deterrence, highlighting the limitations of overreliance on punitive measures and underscoring the importance of addressing drivers’ moral disengagement to enhance pedestrian safety.